Building a scale of sustainable development dimensions for kindergarten students (Journal of the College of Basic Education, 2026)
The current ,research ,aims to develop scale of sustainable development dimensions among female students in the Kindergarten Department. The current research community consists of female students in the Kindergarten Department at the College of Basic Education at the University of Kufa, with a total number of (205) students. The researcher applied the scale of sustainable development dimensions to a sample of 200 students. To verify the research objectives, the two researchers developed a scale of sustainable development dimensions among female students in the Kindergarten Department, which was based on Carney's theory. The scale consisted of (48) paragraphs, with the aim of extracting the psychometric properties of the scale, such as validity and reliability. The data were analyzed and processed statistically using the Statistical Package for Psychological and Social Sciences (SPSS). The researchers concluded with a set of recommendations and proposals.